Effects of oxaliplatin on mouse myenteric neurons and colonic motility - Wafai, Linah; Taher, Mohammadali; Jovanovska, Valentina; Bornstein, Joel C.; Dass, Crispin R.; Nurgali, Kulmira (Frontiers in Neuroscience, 2013)
Oxaliplatin, an anti-cancer chemotherapeutic agent used for the treatment of colorectal cancer, commonly causes gastrointestinal side-effects such as constipation, diarrhoea, nausea and vomiting. Damage to enteric neurons may underlie some of these gastrointestinal side-effects, as the enteric nervous system controls the functions of the bowel. In this study, neuronal loss and changes to the structure and immunoreactivity of myenteric neuronal nitric oxide synthase (nNOS) neurons were examined in colonic segments from mice following exposure to oxaliplatin ex vivo and following repeated intraperitoneal injections of oxaliplatin over 3 weeks in vivo, using immunohistochemistry and confocal microscopy. Significant morphological alterations and increases in the proportion of NOS-immunoreactive neurons were associated with both short-term oxaliplatin exposure and long-term oxaliplatin administration, confirming that oxaliplatin causes changes to the myenteric neurons. Long-term oxaliplatin administration induced substantial neuronal loss that was correlated with a reduction in both the frequency and propagation speed of colonic migrating motor complexes in vitro. Similar changes probably produce some symptoms experienced by patients undergoing oxaliplatin treatment.